Primer registro de marea roja debida a Mesodinium rubrum (Protozoa: Ciliata) en Bahía de Banderas, México - Cortés Altamirano, Roberto; Rodríguez, Rosalba Alonso; Peña Ramírez, Ignacio; Aguilar-Rosas, L. E.; Aguilar-Rosas, M. A.; Aguilar-Rosas, R.; Mendoza-González, A. C.; Aguilar, C. S.; Godínez-Domínguez, E.; Ramos, Gabriel E.; Ríos, Raúl; Salgado-Barragán, José; et al. (Revista de Biología Tropical, 1996)
Contiene los siguientes títulos: Primer registro de marea roja debida a Mesodinium rubrum (Protozoa: Ciliata) en Bahía de Banderas, México Nuevos registros de algas marinas para el Caribe Mexicano Presencia del pulpo Octopus hubbsorum (Cephalopoda: Octopoda) en el Pacífico Central mexicano First record of the genus Excorallana (Isopoda: Corallanidae) in the neritic waters from Pacific of Colombia Decapod crustaceans from the Pacific coast of Mexico, including new records and taxonomic remarks New and additional records of Leptophlebiidae (Ephemeroptera) from Rio de Janeiro State, Brazil New records of Scaris habena and S. pubescens (Homoptera: Cicadellidae) from Brazil First record of the whitetip reef shark, Triaenodon obesus in the west coast of México (Revillagigedo Archipelago) Primer registro de Alopias pelagicus en el Golfo de California, México First record of hermaphroditic specimens of Caulolatilus affini,\' (Pisces: Branchiostegidae) from the Gulf of California